2022
DOI: 10.3390/ani12040435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nutritional Supplement (DìRelaxTM) on Anxiety in Dogs in a Randomized Control Trial Design

Abstract: This study aimed to investigate the efficacy of DìRelaxTM, a nutraceutical formulated to reduce anxiety in dogs, using a randomized controlled trial (RCT) design. The C-BARQ questionnaire, some clinical investigations, and the impossible task test were performed in dogs before and after treatment. The C-BARQ questionnaire is particularly useful for assessing the frequency and severity of problematic behaviors. The impossible task paradigm provides insight into the decision-making processes in the realm of exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, in the case of TSH, fT4, and TT3, previous studies have reported the use of these methods in dogs. [42][43][44][45][46][47][48] Additionally, for all of the methods applied, internal validation demonstrated good accuracy (coefficient of variation < 7%). The decision to make the sample population as homogeneous as possible in terms of age, physical activity, and breed certainly lent more robustness to the correlations identified but decreased the possibility of identifying subjects that, because of borderline thyroid function, had cycle phase-related variability that may have affected the proper diagnosis of euthyroidism.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, in the case of TSH, fT4, and TT3, previous studies have reported the use of these methods in dogs. [42][43][44][45][46][47][48] Additionally, for all of the methods applied, internal validation demonstrated good accuracy (coefficient of variation < 7%). The decision to make the sample population as homogeneous as possible in terms of age, physical activity, and breed certainly lent more robustness to the correlations identified but decreased the possibility of identifying subjects that, because of borderline thyroid function, had cycle phase-related variability that may have affected the proper diagnosis of euthyroidism.…”
Section: Discussionmentioning
confidence: 86%
“…This situation represents another limitation. However, in the case of TSH, fT4, and TT3, previous studies have reported the use of these methods in dogs 42‐48 . Additionally, for all of the methods applied, internal validation demonstrated good accuracy (coefficient of variation < 7%).…”
Section: Discussionmentioning
confidence: 92%
“…The arena contained three chairs (for the owner, the veterinary behaviorist and a cameraperson), a bowl for fresh water and some toys( Figure S1 ). All objects were thoroughly washed after each test to eliminate any olfactory interference, similar to the procedure of Scandurra et al [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over-the-counter commercially available products, including pheromone-based substances, are commonly reported to reduce signs of stress in dogs; however, responses are not consistent across individuals ( Gaultier et al., 2005 ; Gandia Estellés and Mills, 2006 ; Mariti et al., 2012 ). Additionally, a number of nutraceuticals have been evaluated for their anxiolytic effects in dogs, both in the form of supplements ( Beata et al., 2007 ; Bosch et al., 2009 ; Landsberg et al., 2015 ; Cannas et al., 2021 ; Masic et al., 2021 ; Scandurra et al., 2022 ) as well as within complete and balanced diets ( Palestrini et al., 2010 ; Kato et al., 2012 ; Sechi et al., 2017 ), with varying results.…”
Section: Introductionmentioning
confidence: 99%